Draft Annual Plan 1983-84 Union Territory of Dadra and Nagar-Haveli - Planning Commission (Planning Commission, 1983)
As indicated in the detailed write-up of the Plan activities of various development heads included in the Annual Plan 1983-84, this U.T. is mainly dependent on agriculture and allied services. Next to that comes forest activities and hence a great deal of emphasis is continued to be laid on these sectors in addition to other developmental activities. Under the agricultural development numerous schemes provide assistance in the form of subsidy and loan at varying rates for seeds, manure and fertilisers, agricultural implements and commercial crops, etc.
Union Territory of Dadra and Nagar-Haveli, Planning Division Administration